2009
DOI: 10.1111/j.1601-183x.2008.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in brain‐derived neurotrophic factor and human fear conditioning

Abstract: Brain-derived neurotrophic factor (BDNF) has been implicated in hippocampal-dependent learning processes, and carriers of the Met allele of the Val66Met BDNF genotype are characterized by reduced hippocampal structure and function. Recent nonhuman animal work suggests that BDNF is also crucial for amygdala-dependent associative learning. The present study sought to examine fear conditioning as a function of the BDNF polymorphism. Fifty-seven participants were genotyped for the BDNF polymorphism and took part i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
69
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 47 publications
14
69
2
1
Order By: Relevance
“…Results indicated that generalization of conditioned fear to perceptually similar stimuli was indeed evident during the generalization phase. In line with previous studies of human fear generalization (Hajcak et al, 2009;Lissek et al, 2008;Lissek et al, 2010), we found that startle magnitude was largest to the CS+ and then gradually decreased as stimuli became less perceptually similar to the CS+. More specifically, compared to the safest stimulus (CS±60), potentiation of startle occurred to the CS+ and generalized to the next most similar shape (CS±20).…”
Section: Startle Response During Generalizationsupporting
confidence: 92%
See 2 more Smart Citations
“…Results indicated that generalization of conditioned fear to perceptually similar stimuli was indeed evident during the generalization phase. In line with previous studies of human fear generalization (Hajcak et al, 2009;Lissek et al, 2008;Lissek et al, 2010), we found that startle magnitude was largest to the CS+ and then gradually decreased as stimuli became less perceptually similar to the CS+. More specifically, compared to the safest stimulus (CS±60), potentiation of startle occurred to the CS+ and generalized to the next most similar shape (CS±20).…”
Section: Startle Response During Generalizationsupporting
confidence: 92%
“…Using the same generalization paradigm mentioned previously (Lissek et al, 2008), results indicated that PD patients exhibited startle potentiation to the CS+, and this generalized to the three closest CS-(Class 4, 3, and 2), which resulted in a fear response gradient that was less steep than that of healthy controls (Lissek et al, 2009). Controls also exhibited startle potentiation to the CS+, but it only generalized to the one closest CS-(Class 4), which resulted in a steep and curvilinear generalization gradient that is typical of non-clinical humans and non-human animals (Hajcak et al, 2009;Lissek et al, 2009). Hence, both startle data and self-reported risk ratings indicated an overgeneralization of conditioned fear in PD.…”
Section: Fear Generalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hajcak and colleagues (Hajcak et al, 2009) investigated the influence of BDNF on conditioned fear generalization in humans. Fifty-seven participants were genotyped and classified as carriers of the Val/Val BDNF allele (n = 44; 25 female), carriers of the Val/Met allele (n = 4; 3 female) or carriers of the Met/Met allele (n = 3; 1 female).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…The possible role of conditioned fear-generalization in pathological anxiety has gained increased research recognition during the last decade (Vervliet, Vansteenwegen, & Eelen, 2004;Vervliet, Vansteenwegen, Baeyens, Hermans, & Eelen, 2005;Lissek et al, 2008bLissek et al, , 2010Lissek et al, , 2013Hajcak et al, 2009). Indeed, recent etiological accounts of anxiety disorders suggest that conditioned fear-generalization could be a central pathogenic marker of some anxiety disorders (Lissek, 2012), although prospective studies supporting this assumption are lacking.…”
Section: Introductionmentioning
confidence: 99%